Molybdenum-modified iron oxides mediated enhanced degradation of meropenem by peroxydisulfate - Gwangmin Kim; Ayoung Choi; Haesung Lee; Libor Machala; Minhee Kim; Pinelopi P. Falara; Michaela Polaskova; Petr Novak; Nikolaos Ioannidis; George Mitrikas; Virender K. Sharma; Mallikarjuna N. Nadagouda; et al. (Chemical Engineering Journal, 2025)

Development of tungsten-modified iron oxides to decompose an over-the-counter painkiller, Acetaminophen by activating peroxymonosulfate - Aebin Sin; Libor Machala; Minhee Kim; Zdeněk Baďura; Martin Petr; Michaela Polaskova; Petr Novak; Mallikarjuna N. Nadagouda; Dionysios D. Dionysiou; Changseok Han (Science of The Total Environment, 2024)

Revealing the nuclearity of iron citrate complexes at biologically relevant conditions - Maria Gracheva; Zoltán Klencsár; Zoltán Homonnay; Ádám Solti; László Péter; Libor Machala; Petr Novak; Krisztina Kovács (BioMetals, 2024)
Citric acid plays an ubiquitous role in the complexation of essential metals like iron and thus it has a key function making them biologically available. For this, iron(III) citrate complexes are considered among the most significant coordinated forms of ferric iron that take place in biochemical processes of all living organisms. Although these systems hold great biological relevance, their coordination chemistry has not been fully elucidated yet. The current study aimed to investigate the speciation of iron(III) citrate using Mössbauer and electron paramagnetic resonance spectroscopies. Our aim was to gain insights into the structure and nuclearity of the complexes depending on the pH and iron to citrate ratio. By applying the frozen solution technique, the results obtained directly reflect the iron speciation present in the aqueous solution. At 1:1 iron:citrate molar ratio, polynuclear species prevailed forming most probably a trinuclear structure. In the case of citrate excess, the coexistence of several monoiron species with different coordination environments was confirmed. The stability of the polynuclear complexes was checked in the presence of organic solvents.

Incorporating high-resolution climate, remote sensing and topographic data to map annual forest growth in central and eastern Europe - Jernej Jevšenak; Marcin Klisz; Jiří Mašek; Vojtěch Čada; Pavel Janda; Miroslav Svoboda; Ondřej Vostarek; Vaclav Treml; Ernst van der Maaten; Andrei Popa; Ionel Popa; Marieke van der Maaten-Theunissen; et al. (Science of The Total Environment, 2024)

First-in-Rat Study of Human Alzheimer’s Disease Tau Propagation - Tomas Smolek; Santosh Jadhav; Veronika Brezovakova; Veronika Cubinkova; Bernadeta Valachova; Petr Novak; Norbert Zilka (Molecular Neurobiology, 2019)

The last population of the Woodland Brown butterfly (Lopinga achine) in the Czech Republic: habitat use, demography and site management - Martin Konvicka; Jan Novak; Jiri Benes; Zdenek Fric; Jonathan Bradley; Petr Keil; Jan Hrcek; Karel Chobot; Pavel Marhoul (Journal of Insect Conservation, 2008)

The last population of the Woodland Brown butterfly (Lopinga achine) in the Czech Republic: habitat use, demography and site management - Martin Konvicka; Jan Novak; Jiri Benes; Zdenek Fric; Jonathan Bradley; Petr Keil; Jan Hrcek; Karel Chobot; Pavel Marhoul (Journal of Insect Conservation, 2008)